Improving English Vocabulary Mastery Through Duolingo Application For Grade 5 At SD Inpres Kayu Putih - Patrisius Dake; Rozita Yusniaty Lodo; Agnes O. Manek (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
This study investigates the effectiveness of the Duolingo application in improving the English vocabulary mastery of fifth-grade students at SD Inpres Kayu Putih, Oesao II, Kupang Timur District, Kupang Regency, East Nusa Tenggara. This research is based on vocabulary learning theories that emphasize the importance of vocabulary in language acquisition (Nation, 2013; Schmitt, 2010), as well as the theory of Mobile-Assisted Language Learning (MALL), which supports the use of digital applications in language education. Duolingo also utilizes gamification elements to enhance student motivation in learning. The research employed a quantitative quasi-experimental design involving two groups: an experimental group taught using the Duolingo application and a control group taught through conventional methods. Data were collected through pre-tests, post-tests, classroom observations, and student questionnaires. Statistical analysis using an independent samples t-test revealed a significant difference between the two groups (t = 4.208, p < 0.05), with the experimental group achieving a higher mean post-test score (M = 84.27) compared to the control group (M = 68.80). The effect size (Cohen’s d = 1.54) indicated a strong impact of Duolingo on vocabulary mastery. Questionnaire results further showed that students perceived Duolingo as enjoyable, motivating, and effective for learning new vocabulary. The findings suggest that integrating Duolingo into English instruction enhances both learning outcomes and student engagement. Therefore, the application can serve as an effective supplementary tool for teaching vocabulary to young learners in elementary education.